An Examination of the Relationship between Intellectual Capital and Supply Chain Integration in Humanitarian Aid Organizations: A Survey‐Based Investigation of Food Banks. (23rd November 2017) - Ataseven, Cigdem; Nair, Anand; Ferguson, Mark
ABSTRACT: Food banks are humanitarian aid organizations that collect, organize, and deliver food to nonprofit member agencies and also to individuals to help alleviate the society's hunger problem. The supply chain of food banks is characterized by private sector companies, individual donors and governmental agencies providing monetary support and food inventory on the supply side, and the member agencies such as food pantries, soup kitchens, shelters, and volunteers delivering support on the demand side. Within the purview of this supply chain, food banks strive to improve their performance, which is commonly measured in terms of the amount of food delivered to the communities in need. Food banks rely on managerial talent that is relatively more constrained than the private sector and also use a voluntary workforce for attaining their performance goals. Considering the unique yet pertinent role of human assets in food banks to manage their supply chain integration initiatives, we employ an intellectual capital framework to analyze the human, organizational, and social capital antecedents of supply chain integration in food banks. Specifically, we suggest that intellectual capital drives supply chain integration in humanitarian organizations. Moreover, we propose specific relationships between the dimensions of intellectual capital. A carefully crafted survey is used to inform our results. The results indicate that human capital significantly impacts social capital, which, in turn, drives all supply chain integration dimensions. We discuss the implications of our findings for managing intellectual capital in the not‐for‐profit sector and offer directions for future research.